A Single-Phase Multilevel Current-Source Converter using H-Bridge and DC Current Modules - Suroso Suroso; Toshihiko Noguchi (Institute of Advanced Engineering and Science, 2014)
This paper presents a differenttopology ofH-bridge based multilevel current-source inverter (CSI). In this new topology, an H-bridge CSI is connected with a single or more current modules to generate a multilevel output current waveform with lower di/dt, and less distortion. Using the proposed multilevel CSI, the number of the power switching devices, and isolated gate drive circuits can be reduced. Moreover, chopper based DC current sources are presented to reduce the inductor size effectively to be in micro-Henry order, and ensure the balance of the intermediate current levels. The proposed topology is inherently able to reduce the inductor conduction losses if compared with the conventional multilevel CSIs and the H-bridge CSI. Seven-level PWM inverter configurationswith non-isolated DC current sources and with a single DC power source are verified through computer simulations. Furthermore,laboratoryprototypes of seven-level CSI is setup and tested.The results show that the inverter circuit works properly to generate the multilevel output current waveform with low harmonics currents, small inductors and with less conduction losses which proves feasibility of the proposed multilevel CSI. DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5603